2011
DOI: 10.1007/s11657-011-0061-0
|View full text |Cite
|
Sign up to set email alerts
|

PRO-OSTEO Project (improving osteoporosis management in the acute hospital setting): a pilot single-centre study

Abstract: An algorithm-based approach linked with academic detailing and education of the multidisciplinary team in acute hospital environment provides a clinically significant and effective strategy to improve osteoporosis management of patients with minimal trauma fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 26 publications
3
8
0
Order By: Relevance
“…Firstly, the study was undertaken in a single health network covering three rehabilitation sites and two acute hospitals with a wide variety of medical and surgical practices, but located within one area of one Australian state. However, population of PRO‐OSTEO Extend I was similar to populations described in other osteoporosis studies . The rates of pre‐existing minimal‐trauma fractures without any therapy initiated in primary care or during hospitalisation were similar to regional NSW population described in a study from 5 years ago .…”
Section: Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…Firstly, the study was undertaken in a single health network covering three rehabilitation sites and two acute hospitals with a wide variety of medical and surgical practices, but located within one area of one Australian state. However, population of PRO‐OSTEO Extend I was similar to populations described in other osteoporosis studies . The rates of pre‐existing minimal‐trauma fractures without any therapy initiated in primary care or during hospitalisation were similar to regional NSW population described in a study from 5 years ago .…”
Section: Discussionsupporting
confidence: 73%
“…In 2010, an academic detailing and algorithm‐based approach, the PRO‐OSTEO project, was trialled at Peninsula Health's orthopaedic ward. This pilot study demonstrated highly improved assessment and treatment rates, in accordance with current guidelines . However, subsequent audits have shown that sustainability of the project results have been a challenge, with a decline in both assessment and treatment rates observed in association with the loss of an osteoporosis nurse position, and the orthopaedic team's lack of familiarity with secondary prophylaxis and non‐surgical management of the condition.…”
Section: Introductionsupporting
confidence: 59%
See 3 more Smart Citations